Modeling of the Material Behaviour of Magnesium Alloy AZ31 Using Different Yield Criteria - Banabic, Dorel; Hußnätter, Wolfgang (International Journal of Advanced Manufacturing Technology, 2009)
Nowadays, the finite element analysis (FEA) is playing a main rule in fields of sheet metal forming for designing processes and dimensioning parts. The most frequent yield criteria used in the FE commercial programs for the sheet-metal-forming simulation, like AUTOFORM, PAMSTAMP, etc., are Hill'48 for common steels or Barlat'89 and various BBC models for some aluminum alloys. In this paper, different yield loci for biaxial tensile stress conditions of the magnesium sheet metal alloy AZ31 are investigated. The experimental investigations have been done using the specimen geometry for the experimental setup developed at the Chair of Manufacturing Technology (LFT) of the University of Erlangen. The yielding behavior is determined basing exclusively on real material data out of experiments so that no FE calculations are necessary to detect strains and stresses. Using these data, several yield criteria are applied to approximate the real material characteristics, whereas the model of BBC'2005 leads to the best agreement for uniaxial yield stresses, the anisotropy coefficients, and the yield locus. © 2009 Springer-Verlag London Limited.
LFT Import::2019-07-29 (1569)
Keywords: BBC'2005; Material characterization; Yield criterion; Yield locus diagram